Pathways to transformation : learning in relationship - Boden, Carrie J.; Kippers, Sola M. (Innovative perspectives of higher education., 2012)
Pathways to Transformation: Learning in Relationship is an edited collection that synthesizes current research on transformative learning and expands the current knowledge-base. This book is timely and significant as it provides a synthesis of some of the most exciting research in two fields: adult education and human services.The objectives of this themed edited collection, Pathways to Transformation: Learning in Relationship, are threefold. First, this collection serves as a space to synthesize current research on transformative learning. Through an extensive literature review, the editors have discerned several important strands of research in the area of transformative learning and solicited chapters dealing with these topics. The second objective of the collection is to expand the current knowledge-base in the area of transformative learning by creating a space for dialog on the subject and bringing together diverse voices. The third objective of the collection is to transcend the field of adult education, with a specific goal to reach an audience in human services (psychology, counseling, social work, marriage and family therapy).